Differences in cell subsets between sun-exposed and unexposed skin: preliminary single-cell sequencing and biological analysis from a single case - Zhou, Feng; Sun, Yu; Chen, Xinling; Hou, Wenyi; Shen, Jing; Lai, Wei; Han, Kai; Zheng, Yue (Frontiers in Medicine, 2024)
Introduction The composition and subsets of skin cells continuously change in a dynamic manner. However, the specific microcosmic alterations of human photoaged skin, independent of chronologic aging, remain unclear and have been infrequently analyzed. This study aimed to evaluate the biological processes and mechanisms underlying cell-subgroup alterations in skin photoaging. Methods We utilized single-cell sequencing and biological analysis from a single case to investigate the effects of photoaging. Skin punch biopsies were taken from sun-exposed forearm skin and unexposed buttock skin from the same individual for comparative analysis. Results Our analysis identified 25 cell clusters and 12 skin cell types, revealing significant changes in unique gene expressions between the sun-exposed and unexposed skin samples. A comparison of cell numbers within each cluster revealed 9 dominant cell clusters in sun-exposed skin and 16 dominant cell clusters in unexposed skin. Enrichment analysis indicated that PD-L1 expression and the PD-1 checkpoint pathway were more prominent in sun-exposed skin, while MAPK, TNF-alpha, TGF-beta, and apoptosis pathways were more enriched in hair follicle cells of sun-exposed skin. Discussion This study reveals changes in cell components in photoaged skin from a single case and provides novel insights into cellular subpopulations and pathology during repeated UVA-induced skin damage. These findings enhance our understanding of the complex interplay between different cells in photoaged skin and offer potential targets for preventing human skin photoaging and UV-induced skin cancers.